2017
DOI: 10.1016/j.ajpath.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Brown Adipose–Like Tissue in Trauma-Induced Heterotopic Ossification in Humans

Abstract: Heterotopic ossification (HO), the abnormal formation of bone within soft tissues, is a major complication after severe trauma or amputation. Transient brown adipocytes have been shown to be a critical regulator of this process in a mouse model of HO. In this study, we evaluated the presence of brown fat within human HO lesions. Most of the excised tissue samples displayed histological characteristics of bone, fibroproliferative cells, blood vessels, and adipose tissue. Immunohistochemical analysis revealed ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Surprisingly, one of the first steps observed in early neurogenic HO (even prior to the appearance of bone matrix) is the biogenesis of brown adipocyte-like cells (tBAT) [81, 82, 83]. BAT is a unique form of adipose tissue induced by cold exposure with the unique feature that it expresses uncoupling protein 1 (UCP1) in mitochondria that uncouples the ATPase from the other complexes of electron transport.…”
Section: Brown Adipocytes a Key Component Of Neurogenic Homentioning
confidence: 99%
“…Surprisingly, one of the first steps observed in early neurogenic HO (even prior to the appearance of bone matrix) is the biogenesis of brown adipocyte-like cells (tBAT) [81, 82, 83]. BAT is a unique form of adipose tissue induced by cold exposure with the unique feature that it expresses uncoupling protein 1 (UCP1) in mitochondria that uncouples the ATPase from the other complexes of electron transport.…”
Section: Brown Adipocytes a Key Component Of Neurogenic Homentioning
confidence: 99%
“…At the same time, brown adipogenesis was occurring ( 17 ), and the newly formed adipocytes expressed uncoupling protein 1 (UCP1), a hall mark of brown adipose tissue. Recently, we reported that these same cells were present in humans during early HO associated with traumatic injury ( 18 ).…”
Section: Induction Of Ho Coincides With Changes In the Bnbmentioning
confidence: 86%
“…tBAT is an energy powerhouse and uses UCP1 to create a hypoxic microenvironment for chondrogenesis ( 27 ), but also secretes angiogenic molecules ( 28 ). We have recently described its presence in humans ( 18 ). tBAT and chondrocytes appear closely related and tBAT clearly arises from the endoneurium ( 26 ), yet traverses through the perineurium ( 17 ).…”
Section: Neural Crest Derived Osteogenic Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations